2000
DOI: 10.1021/ic9912878
|View full text |Cite
|
Sign up to set email alerts
|

Control of Oxo-Molybdenum Reduction and Ionization Potentials by Dithiolate Donors

Abstract: The compounds (L-N3)MoO(qdt) and (L-N3)MoO(tdt) [(L-N3) = hydrotris(3,5-dimethyl-1-pyrazolyl)borate; tdt = toluene-3,4-dithiolate; qdt = quinoxaline-2,3-dithiolate] have been studied by cyclic voltammetry and photoelectron, magnetic circular dichroism, and electronic absorption spectroscopies, and the experimental data have been interpreted in the context of ab initio molecular orbital calculations on a variety of dithiolate dianion ligands. The PES data reveal very substantial differences between (L-N3)MoO(qd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 44 publications
2
76
0
Order By: Relevance
“…That the specific substituents on the dithiolene can have an enormous effectalmost 1 V-on the Mo reduction potential has been previously noted [15,47].…”
Section: Characterization Of Mono-pterin-dithiolene Molybdenum Complexesmentioning
confidence: 78%
See 1 more Smart Citation
“…That the specific substituents on the dithiolene can have an enormous effectalmost 1 V-on the Mo reduction potential has been previously noted [15,47].…”
Section: Characterization Of Mono-pterin-dithiolene Molybdenum Complexesmentioning
confidence: 78%
“…Furthermore, detailed electronic absorption, MCD, and EPR studies have been performed on related oxomolybdenum mono-dithiolene complexes, and the new studies reported herein provide a context in which to interpret the effects of a pterin substituent on the electronic structure of the coordinated dithiolene in the enzymes [15,[48][49][50][51][52][53].…”
Section: Spectroscopic Studiesmentioning
confidence: 99%
“…3) at 7.04 eV is similar in appearance to the low energy band of related complexes having alkoxide ligands (23,52) that has been assigned to ionization arising primarily from the half-filled metal-based orbital (21, 23, 52). The two ionizations between 7.25 eV to 8.00 eV can then be assigned to ionizations associated with symmetric (S ϩ ) and antisymmetric (S Ϫ ) combinations of S orbitals based on previous assignment of analogous complexes (21,22). More detailed assignment of the S ϩ and S Ϫ ionizations is not possible because of the significant overlap of these low-energy features and the beginning of the Tp* ligand based ionizations.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent photoelectron spectroscopic studies of other pairs of (Tp*)MoE(dithiolate) complexes (E ϭ O, NO) have shown that the first ionization energies of the members of each pair are within Ϸ0.2 eV of one another. For a series of (Tp*)MoO(dithiolate) complexes with varying peripheral substitutions on the dithiolate ligand, the first ionization energies show a range of Ϸ0.7 eV and correlate with the lowest energy oxidation potential in solution (11,22). Gas-phase photoelectron spectroscopy avoids possible complications of solvent and solid state effects, but a major drawback is that only neutral species are easily studied by this technique, and the (Tp*)MoO(dithiolate) system does not allow access to the important d 0 and d 2 electron configurations of the catalytic cycle.…”
mentioning
confidence: 99%
“…Evolutionary conservation of the molybdopterin ligand is strong evidence that it serves an important function to the metal site in catalysis. Features unique to a dithiolene chelate which might be important to the Mo and W cofactors have been identified by a considerable number of coordination chemistry studies comparing dithiolene with other sulfur donor ligands [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%